PSYCHOLOGICAL QUALITIES THAT DETERMINE SUCCESS COMPETITIVE ACTIVITY THE ATHLETE - Babushkin, Gennady; Bobrovsky , Vladislav; Kraynik, Victor; Elena, Romanova; Moshkov, Mikhail; Krestyaninov, Viktor; Babushkin , Eugene (Revista Inclusiones, 2020)
The article is devoted to the study the influence of psychological qualities on the success of competitive activity of athletes. Observation of performance of athletes of various qualification at competitions of various rank (weightlifters, swimmers, skaters, shooters from the gun) for the purpose of identification of success of performance is carried out. A number of athletes identified the average level of development of these qualities that has a negative impact on the pre condition of the athlete and the success of the activities at the event. Athletes who have high rates of these qualities, doing the bidding results, demonstrated at the competition of high sports results, won prizes and had set personal records. In process increase sports qualification influence psychological qualities on success performance athletes increases.